ANALISIS ADVOKASI MEREK TERHADAP MINAT PEMBELIAN - Lingga Yuliana (Politeknik Ubaya, 2022)
Abstract The high level of consumer engagement for shopping is a chance for local business owners to sell products that are in line with consumer demand. Purposive sampling is employed in this research together with a descriptive quantitative methodology. The number of respondents involved are two people who are marketing enthusiasts and consumers of Valencia by Enrica products who have started buying products since 2017 until now. The Analytic Network Process was the analytical tool utilized in this research.The node Intention to try a new product became the top node of and 0.639752, 0.538738, and 0.63975 based on the Synthesis Value, Limiting Value, and Normalized by Cluster on Brand Advocacy. The Preferential Interest Node becomes the best node in Normalized by Cluster on Purchase Interest at 0.57344. Valencia by Enrica brand advocacy endeavors are expected to have an influence on consumer interest in purchasing footwear by attracting buyers with innovative and high-quality goods.